The Role of Work Motivation in Mediating the Effect of the Work Environment on Employee Performance - Anjani Putri Utami, Ema; Yuliana, Ika; Makiah, Makiah; Cahyadi, Irwan; Nurmelia Marlini, Febria (Universitas Fajar, 2026)
This study aims to analyze the influence of the work environment on employee performance with work motivation as a mediating variable at PT Kijang Lombok Raya. The approach used in this research is quantitative, employing an associative-causal design. The sample consists of 50 active employees selected using a total sampling method. Data were collected via Likert-scale questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that the work environment has no direct and significant effect on employee performance. However, the work environment significantly affects work motivation, which in turn has a significant effect on employee performance. Additionally, work motivation has been shown to significantly mediate the relationship between the work environment and employee performance. These findings suggest that improving employee performance requires not only a supportive work environment but also strong intrinsic and extrinsic motivation. Therefore, company management is recommended to enhance employee motivation by providing adequate workplace facilities, supportive leadership, and a positive organizational culture to foster optimal performance.